2014
DOI: 10.3126/njms.v3i1.10341
|View full text |Cite
|
Sign up to set email alerts
|

Community Urinary Tract Infection due to ESBL producing E. coli: epidemiology and susceptibility to oral antimicrobials including Mecillinam

Abstract: Background: There is increasing incidence of (Extended spectrumbeta lactamases) ESBL producing E. coli causing community urinary tract infections (UTI). The primary objective of this study was to study the epidemiological factors associated with ESBL positive community acquired uropathogenic E. coli isolates and to determine their susceptibility to newer oral drugs including mecillinam. Methods: In this prospective study, from total of 140 community isolates of E. coli causing UTI, ESBL was detected by Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…This is in correlation with other studies such as Mahesh et al, (2010) and Chaudhary et al, (2013) who reported 56.2% and 54.5% ESBL production in E. coli isolates respectively. However our findings are in contrast with other studies conducted by Datta et al, (2014) Dugal et al, (2013 DMBT Dissanayake et al, (2012) and Singh et al, (2016) who reported 21.4%, 24.4%, 29% and 82.6% ESBL producing E. coli isolates respectively.…”
Section: Resultscontrasting
confidence: 57%
“…This is in correlation with other studies such as Mahesh et al, (2010) and Chaudhary et al, (2013) who reported 56.2% and 54.5% ESBL production in E. coli isolates respectively. However our findings are in contrast with other studies conducted by Datta et al, (2014) Dugal et al, (2013 DMBT Dissanayake et al, (2012) and Singh et al, (2016) who reported 21.4%, 24.4%, 29% and 82.6% ESBL producing E. coli isolates respectively.…”
Section: Resultscontrasting
confidence: 57%
“…ESBL-producing bacteria have been increasingly detected in meat from food-producing animals such as, poultry (Ghodousi et al, 2015; Shrestha et al, 2017; Poirel et al, 2018). Our findings have raised significant concerns, since the 30% prevalence of ESBL-producing samples in chicken carcasses in southern Brazil was higher than those reported in other regions, as in USA (27%), in India (21%) and in other samples from Brazil (7%) (Freeman et al, 2009; Datta et al, 2014; Gonçalves et al, 2016). Among all ESBL strains, we found 97% classified as bla CTX−M and the majority belonged to CTX-M-2 group, although the rates varied depending on the region worldwide.…”
Section: Discussionmentioning
confidence: 61%
“…Out of 291, E. coli isolates, 108 (37.11%) are ESBL-producer and 183 (62.89%) are non-ESBL-producer. Other studies reported a prevalence of ESBL-producer E. coli isolates 46.87% (10), 82.6% (11) and 21.4% (12) respectively. This different results may be due to the difference in the risk factors include recent antibiotic therapy, administration of corticosteroids, hospitalization (13).…”
Section: Discussionmentioning
confidence: 90%